This preview shows pages 1–3. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: MATH 138 Calculus 2, Solutions to Assignment 6 Problem 1: We can sense that ( 3 + 1 n ) 2 9 as n . Given any > 0, show that if n > 7 , then ( 3 + 1 n ) 2 9 < . This proves from scratch that ( 3 + 1 n ) 2 9. Hint. You know that 1 n 2 1 n always. Solution: For n 1 we have n 2 n so 1 n 2 1 n , and we have ( 3 + 1 n ) 2 > (3 + 0) 2 = 9 so ( 3 + 1 n ) 2 9 = ( 3 + 1 n ) 2 9 = ( 9 + 6 n + 1 n 2 ) 9 = 6 n + 1 n 2 6 n + 1 n = 7 n . Thus given > 0, if n > 7 then 7 n < so we have ( 3 + 1 n ) 2 9 7 n < . Problem 2: Find the following sequence limits by using limit properties. It is not necessary to prove your answers by means of thedefinition. (a) lim n n q 1 + 1 n 1 Solution 1: We have lim n n q 1 + 1 n 1 = lim n n q 1 + 1 n 1 q 1 + 1 n + 1 q 1 + 1 n + 1 = lim n n ( 1 + 1 n 1 ) q 1 + 1 n + 1 = lim n 1 q 1 + 1 n + 1 = 1 1 + 0 + 1 = 1 2 . Solution 2: By replacing 1 n by the continuous variable x and then using lH opitals Rule, we have lim n n q 1 + 1 n 1 = lim n q 1 + 1 n 1 1 n = lim x + 1 + x 1 x = lim x + 1 2 1+ x 1 = 1 2 . (We remark that when we replace 1 n by x , we are implicitly using Theorem 12 from the notes on limits of sequences which are posted on UWACE). (b) lim n n 3 q 1 + 1 n 1 . This one might require more imagination. Solution 1: We have lim n n 3 q 1 + 1 n 1 = lim n n ( 1 + 1 n ) 1 / 3 1 ( 1 + 1 n ) 2 / 3 + ( 1 + 1 n ) 1 / 3 + 1 ( 1 + 1 n ) 2 / 3 + ( 1 + 1 n ) 1 / 3 + 1 = lim n n ( 1 + 1 n 1 ) ( 1 + 1 n ) 2 / 3 + ( 1 + 1 n ) 1 / 3 + 1 = lim n 1 ( 1 + 1 n ) 2 / 3 + ( 1 + 1 n ) 1 / 3 + 1 = 1 (1 + 0) 2 / 3 + (1 + 0) 1 / 3 + 1 = 1 3 . Solution 2: By replacing 1 n by the continuous variable x and then using lH opitals Rule, we have lim n n 3 q 1 + 1 n 1 = lim n ( 1 + 1 n ) 1 / 3 1 1 n = lim x + (1 + x ) 1 / 3 1 x = lim x + 1 3 (1 + x ) 2 / 3 1 = 1 3 . 1 (c) lim n (ln(3 + e n )) /n Hint: First explain and then use the identity ln(3 + e n ) = n + ln(1 + 3 e n ) ....
View
Full
Document
This note was uploaded on 03/16/2011 for the course MATH 138 taught by Professor Anoymous during the Winter '07 term at Waterloo.
 Winter '07
 Anoymous
 Calculus

Click to edit the document details